Dermatoscopic imaging of skin lesions by high school students: a cross-sectional pilot study - Michael A. Marchetti; Maira Fonseca; Stephen W. Dusza; Alon Scope; Alan C. Geller; Marilyn Bishop; Ashfaq A. Marghoob; Susan A. Oliveria; Allan C. Halpern (Mattioli1885, 2015)
Background: The ability of novices to perform imaging of skin lesions is not well studied. Objectives: To determine the ability of 12th grade high school students without formal training to take clinical and dermatoscopic images of skin lesions on patient-actors. Patients/Methods: Nineteen participants were divided into 11 gender-specific groups of 1-2 students. Groups were provided written instructions and assessed in their ability to (a) identify 8 pre-specified skin lesions, (b) take overview clinical images, and (c) take contact, polarized dermatoscopic images. Groups captured the same images twice using two different cameras [NikonTM 1 J1 / VEOS HD1 and a VEOS DS3 (Canfield Scientific, Inc.)]. The sequence of camera use was determined using block randomization. If students made visibly poor skin contact during dermatoscopic imaging using their first camera, study investigators provided verbal instructions to place the second camera directly onto the skin. Students completed anonymous surveys before and after the imaging activity. Results: Students were proficient at identifying the correct pre-specified skin lesions (86/88, 98%), capturing sufficient quality overview clinical images of the back and legs (41/42, 98%), and taking dermatoscopic images of the entire skin lesion (174/176, 99%). Regarding dermatoscopic image quality, 116 of 175 (66%) images were in focus. Out of focus images were attributed to poor skin contact. Groups that received feedback (n=4) were able to obtain a significantly higher proportion of in focus dermatoscopic images using their second camera compared to their first camera (16% to 72%, P<0.001). Conclusions: We identified several barriers that exist for participant-acquired dermatoscopic imaging. Instructions emphasizing the importance of skin contact are useful. Our results may help guide future patient-acquired teledermatoscopy efforts.